Primary Cutaneous Mantle Cell Lymphoma: A Case Report - L. D. Mazzuoccolo; G. A. Castro Perez; I. Sorin; A. I. Bravo (Case Reports in Dermatological Medicine)
Primary cutaneous mantle cell lymphoma (MCL) is a rare cutaneous proliferation of naive pregerminal CD-5 positive B cells in the skin with no extracutaneous involvement. Overexpression of cyclin D1 is pathognomonic of this condition, and surgery and radiation therapy are the most common therapeutic options. In this case, we describe the clinical, histopathological, immunohistochemical, and molecular characteristics of a new case of primary cutaneous MCL.